Production of syngas from ethanol CO2 reforming on La-doped Cu/Al2O3 : Impact of promoter loading - Nor Shafiqah, Mohd-Nasir; Nguyen, Trinh Duy; Jun, Lau N.; Mahadi, Bahari; Phuong, Pham T. T.; Bawadi, Abdullah; Vo, Dai-Viet N. (American Institute of Physics Inc., 2019)
Incipient wetness impregnation (IWI) method was applied to prepared 10%Cu/Al2O3 whereas M%La-doped 10%Cu/Al2O3 (Mwt%= 1%, 2%, 3%, 4% and 5%) were synthesized by employing sequential IWI technique. The prepared catalysts were evaluated from ethanol CO2 reforming (ECR) at 1023 K and stoichiometric feed ratio. Average crystallite size of CuO particle is reduced with La-promoter addition probably caused by lanthana dilution effect that prevent agglomeration from occurring within CuO particles. H2 reduction process produce complete CuO reduction and constant signal is appearing beyond 525 K suggests that the catalysts were completely reduced beyond that temperature. 3%La catalyst identified as optimal promoter loading based on reactant conversions. C2H5OH and CO2 conversions were achieved on 3%La loading is 87.6% and 55.1%, respectively. Carbon was identified on catalyst surface based on X-ray diffraction (XRD) and scanning electron microscopy (SEM).